Integrating the IR into strategic goals at the University of Toledo: case study. Issue 4 (13th November 2017) - Sabharwal, Arjun; Natal, Gerald R.
Abstract : Purpose: The purpose of this case study is to demonstrate a current model, as well as explore future models, for integrating institutional repositories (IRs) in higher education goals at the University of Toledo. Design/methodology/approach: This is a case study that uses literature review as an exploratory framework for new approaches while reflecting on existing literature to present the current practical framework for using IRs. Findings: The digital environment has pushed academic institutions toward new strategies for curating their record on scholarship and preserving their heritage collections, using their IRs. Innovative approaches are also vital to curating the IR content digitally to facilitate access to those contents in ways that was not possible a few decades ago. Surveys and existing literature point to increasing uses of IRs despite abstinence from considering open access for scholarly activity among faculty concerned about copyright, plagiarism and sustainability. Staffing and funding IR initiatives are important factors in sustaining the curation of scholarship in the digital environment. Practical implications: IRs with open access publishing, expert gallery and digital library features place academic libraries in a central role as partners in digital scholarship. Originality/value: This case study presents an original approach to incorporating the IR into the curation of digital content while also considering potential uses of knowledge management approaches for data and knowledge sharing in an academic environment.